An Open-Label Uncontrolled, Multicenter Study for the Evaluation of the Efficacy and Safety of the Dermal Filler Princess VOLUME in the Treatment of Nasolabial Folds. (3rd March 2015) - Kopera, Daisy; Palatin, Michael; Bartsch, Rolf; Bartsch, Katrin; O'Rourke, Maria; Höller, Sonja; Baumgartner, Renate R.; Prinz, Martin
Abstract : The dermal filler Princess VOLUME is a highly cross-linked, viscoelastic hyaluronic acid injectable gel implant used for aesthetic treatment. To evaluate the efficacy and safety of Princess VOLUME in the treatment of nasolabial folds, an open-label uncontrolled, multicenter study was conducted. Forty-eight subjects were recruited who had moderate to deep wrinkles, according to the Modified Fitzpatrick Wrinkle Scale (MFWS). Subjects received Princess VOLUME in both nasolabial folds at Day 0. Nasolabial fold severity was evaluated at 30, 90, 180, and 270 days after treatment, using the MFWS and the Global Aesthetic Improvement Scale (GAIS). Adverse events and treatment site reactions were recorded. Among the 48 subjects, 93.8% were female with a median age of 52 years. There were significant improvements ( P < 0.0001 ) in the MFWS scores at 30, 180, and 270 days after treatment compared with those at baseline, with a mean decrease of 1.484 (±0.408), 1.309 (±0.373), and 1.223 (±0.401), respectively; hence the primary endpoint was achieved and clinical efficacy demonstrated. Princess VOLUME was well tolerated, and most adverse events were injection site reactions of mild to moderate severity. Subject satisfaction (97.9%), subject recommendation of the treatment (93.6%), and investigators GAIS scores (97.9% improvement) were high.